(untitled) (Research, Society and Development, 2022)
Biodiesel is considered a renewable fuel produced from vegetable oils or animal fats and is used in vehicles equipped with diesel cycle engines. This fuel was introduced in the Brazilian energy matrix through law 11.097/05, assigning to the National Agency of Petroleum, Natural Gas and Biofuel (ANP) the specifications for biodiesel, aiming to ensure its quality in compliance with technical standards and norms. Based on this fact, this work aimed to evaluate the sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), phosphorus (P), and sulfur (S) contents in a biodiesel sample produced in the laboratory. Initially, the soybean oil was transesterified and then characterized by the parameters specific mass at 20 ºC and kinematic viscosity at 40 ºC. After this step, the determinations of the proposed elements began. For Na and K the atomic absorption technique was used, Mg, Ca, and P were determined by atomic emission with inductively coupled plasma and the S content by ultraviolet fluorescence. The values of 880 kg/m3, and 4.8 mm2/s for specific mass and viscosity, respectively, were the evidence that methyl esters were produced. The sum for sodium and potassium was 1.03 mg/kg, for calcium and magnesium was 0.22 mg/kg, phosphorus content was 5.00 mg/kg and sulfur content was 1.67 mg/kg. All the results indicate that the biodiesel produced is in accordance with ANP resolution No 45/14 for the investigated parameters.